Faktor-faktor yang Mempengaruhi Risiko Bank pada Bank Komersial di ASEAN - Muhammad Ilham Nurdin, Muhammad Ilham Nurdin; Isni Andriana, Isni Andriana; Mu’izzuddin, Mu’izzuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Operational Efficiency (BOPO), Inflation dan Exchange Rates to Non Performing Loan (NPL). The number of samples in this study is 151 commercial banks in ASEAN which fulfills the sample criteria based on purpoosive sampling method. This study take place over a periode of year 2013-2022. The research method used is data panel regression with Feasible Generalized Least Square estimation. The result of the analysis show that LDR, Inflation and Exchange Rates have negative effect on NPL. CAR and BOPO have a significant positive effect on NPL.